Survey on Important Pests of Rice and Vegetables with Emphasis on Population Trend and its Damage - Soelaksono Sastrodihardjo (Journal of Mathematical and Fundamental Sciences, 1974)
Ringkasan. Telah dilakukan pengamatan tentang komponen serangga dan arthopoda lain pada asosiasi padi dan sayuran. Didapatkan bahwa komponen tersebut masih cukup berarti dari segi rantai interaksi ekologis. Dilakukan penafsiran terhadap pola populasi penggerek batang padi serta serangga hama sayuran dengan cara sampling stadia muda dan dewasa. Diketemukan pola populasi yang tidak begitu bervariasi untuk suatu daerah yang luas di Jawa Barat. Abstract. The insects and other arthropode components of rice and vegetables association were investigated. It was found that these components were still meaningful from the aspect of ecological interaction. Estimate of rice-borers population trend and also of the vegetables pests were carried out by means of immatures and matures sampling. Apparently the variation of the population trend of rice as well as vegetable pests was small within a relatively large area in West Java.